PENCABUTAN KETERANGAN TERDAKWA DALAM BAP DI MUKA SIDANG PANGADILAN (STUDI KASUS DI PENGADILAN NEGERI DENPASAR) - Adhi Parwatha, I Made; Keneng, I Ketut; Sudjana, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
In the middle of court session investigation, to find a material truth, verification is an absolute thing to do, because an that case will investigating proof instruments. Beside of the accused rescind their information given before on the annoucement judicial procedure investigation when verification entering the court session investigation. Rescindation of the information given before will take influence in the time when judge considering the decision.
Keywords: Verification, The accused Information, The Announcement Judicial Procedure Information, Decision